2017
DOI: 10.1097/md.0000000000008153
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological, radiographic, and oncogenic features of primary pulmonary enteric adenocarcinoma in comparison with invasive adenocarcinoma in resection specimens

Abstract: Primary pulmonary enteric adenocarcinoma (PEAC) is a rare subtype of primary lung adenocarcinoma. However, it is not known whether there are any distinctive clinical or molecular features.PEACs were retrospectively identified in 28 patients from July 2014 to June 2016. We compared the clinicopathological, radiographic, and oncogenic characteristics of PEAC and primary pulmonary invasive adenocarcinoma (IAC).A total of 28 PEAC patients and 92 IAC patients were compared. PEAC occurred more frequently in males (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 34 publications
(51 reference statements)
2
59
0
Order By: Relevance
“…IHC features of PAED have been described by several authors, but data are often conflicting and inconclusive ( Refs 13,19,20,23,24,31,34). However, scientific societies agree in considering, as major pathological characteristics of PAED, the IHC positivity for at least one marker of colonic differentiation, among CDX2, CK20 and MUC2, as well as the presence of an entero-like tumour cell morphology in more than half sample (Travis 2013, Truini 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…IHC features of PAED have been described by several authors, but data are often conflicting and inconclusive ( Refs 13,19,20,23,24,31,34). However, scientific societies agree in considering, as major pathological characteristics of PAED, the IHC positivity for at least one marker of colonic differentiation, among CDX2, CK20 and MUC2, as well as the presence of an entero-like tumour cell morphology in more than half sample (Travis 2013, Truini 2015).…”
Section: Discussionmentioning
confidence: 99%
“…spiculation, pleural effusion or indentation) can be similarly detected in PAED and primary pulmonary IAC samples (Ref. 19). Moreover, Bian et al found no significant differences when comparing CT scans from 13 PAED cases with 27 patients with metastatic colorectal cancer (MCC) (Ref.…”
Section: Pathogenesis and Clinical Featuresmentioning
confidence: 95%
See 2 more Smart Citations
“…Also, considering the small number of cases observed, no differences in onset, lung location type, clinical course, and radiographic features between PEAC and conventional lung adenocarcinoma are reported. 3 In contrast to lung cancer, in several cases PEAC shows an increase in circulating tumor markers CA19-9 and carcinoembryonic antigen (CEA) with an absence of CYFRA 21.1 or Neuron Specific Enolase (NSE). 3 With the advance of nucleic acid sequencing technologies over the recent years, new perspectives are emerging in the field of cancer characterization, but the rarity of PEAC hindered the identification of specific molecular signatures to apply in differential diagnosis, prognostic stratification, and prediction of response to therapy.…”
Section: Introductionmentioning
confidence: 99%